Interior Design School of Photography in Surakarta - Annisa Ainul Latifah (Pendhapa, 2022)
Interior Design School of Photography in Surakarta is a space and place for students in the special field of photography. The development of photography technology in Indonesia has caused photography not only to be used as a means to document an event or activity, but photography has also developed into a means or means of communication in the field of art. This final task aims to produce the interior design of the School of Photography with a Modern Natural Concept. Surakarta is one of the student cities in Indonesia. Indonesian society itself has a high interest in photography. Some schools in Indonesia are inadequate in terms of facilities and comfort so that students are less effective in conducting learning and teaching activities. The design method used into two stages. The first stage is data collection, with literature studies and field studies. The second stage is data analysis based on requirements that include space programs, circulation systems, and security systems. The results of the analysis were then combined with the concept of design that has been selected, namely produced an interior design School of Photography with a modern natural concept. The use of modern natural style is expected to be able to optimize between aesthetics and also function in the school with a natural impression.Keyword : School, Photography, Function, Natural, Interior Design.